Italian healthcare workers' views on mandatory vaccination - Tafuri, Silvio ST (BioMed Central, 2009)
BACKGROUND: Mandatory vaccination has contributed to the success of immunisation programmes but voluntary vaccination allows people to be responsible for their own health. There are benefits from both policies and the arguments between them remain subject to debate within and without the scientific community, both nationally and internationally. The aim of this study is to assess the opinions of those who actually work in the Vaccination Service. METHODS: The survey was carried out using a self-administered standardised anonymous questionnaire given to all of the Vaccination Service employees in the Apulia Region. RESULTS: Of 302 completed questionnaire replies, 4.4% stated that mandatory vaccination should be abandoned now, 21.2% that it should be phased out, and 74.4% that it should be retained. CONCLUSION: An educational program should be set up to explain to Vaccination staff the value and worth of voluntary compared to mandatory vaccination and why high vaccination rates do not have to depend on compulsion.